Prevalence of Intestinal Parasitic Infections and Associated Risk Factors among the First-Cycle Primary Schoolchildren in Sasiga District, Southwest Ethiopia. (13th March 2020) - Sitotaw, Baye; Shiferaw, Wakgari
Abstract : Intestinal parasitic infections (IPIs) have been major public health burdens in low-income countries like Ethiopia. Studies in different areas of Ethiopia have shown a high prevalence of IPIs in poor families. A similar study has not been conducted in Sasiga District given that the area is possibly at high-risk of IPIs due to the prevailing risk factors. This study is aimed at assessing the prevalence of IPIs and associated risk factors among schoolchildren in Sasiga District, southwest Ethiopia. A school-based cross-sectional study was conducted from December 2018 to March 2019 to estimate the prevalence of IPIs and associated risk factors among the study participants. A total of 383 children were selected using resident-type and grade-level stratified systematic random sampling technique. Stool samples were examined microscopically using direct wet mount and formal-ether concentration techniques. A structured questionnaire was used to get information on the associated risk factors. Data were analyzed using SPSS version 20 and p value of ≤0.05 was taken as statistically significant. The overall prevalence of IPIs among the children was 62.4% (239/383). Single, double, and triple infections were 49.9%, 10.7%, and 1.83%, respectively. Residence, family income, place of defecation, source of drinking water, shoe-wearing habit, handwashing habit after toilet use, ways of waste disposal, and cleanliness of fingernail were the most important predictors of IPIs (p < 0.05 ). Ascaris lumbricoides (22.7% (87/383)) and hookworms (20.6% (79/383)) were the most prevalent parasites, followed by Entamoeba histolytica (8.1%), Trichuris trichiura (7.6%), Giardia intestinalis (6.5%), Hymenolepis nana (5.7%), and Schistosoma mansoni (4.4%), in that order. Sasiga District primary schoolchildren are likely at a high burden of IPIs. Intensive health education on personal hygiene and environmental sanitation is needed.